학교 신종플루 확산기 동안의 초등학교 보건교사의 직무현황 - 신선미; 김혜순; 홍민순; 이희우; Shin, Sun-Mi; Kim, Hye-Soon; Hong, Min-Soon; Lee, Hee-Woo (韓國學校保健學會誌, 2010)
Purpose: To identify the need to reform in the crisis response of Health Teacher, School Nurse, in elementary school during epidemic outbreak of influenza H1N1. Methods: 139 elementary health teachers, school nurse, in seoul elementary school responded in the questionnaire, and we analysed by using frequency and percent, t-test, and paired t-test. Results: The Job status became 121% more 'during influenza H1N1 (flu) outbreak' than Job status of 'before outbreak'. The proportion of the flu-related duty among their daily workload was up to 77.5%. The administration-related workload of the flu-related duty was 30.8%. and students' health assessment including temperature measurement 18.7%. Furthermore, an impediment of usual daily work due to an increaed flu-related workload was 95.7%, and no alternative plan such as disposition of assistant labor force was 86.1%. Especially, an impediment of health education was 61.0%, so the major concern was the loss of health education. We compared average scores (a five-point Likert scale) of health teachers' work motivation, exhaustion, work relationship and Job management of 'during' with 'before' flu-outbreak. The difference range of 'during' minus 'before' work motivation score was from -0.4 points to -0.9; work exhaustion range from 1.8 to 1.9; the difficulty of relationship between students, school personnel, parents of students, and health teachers from 1.4 points to 1.3 points; and the consideration of changing Job, taking time off from the Job and retirement from 1.4 to 1.6 points. Conclusion: The health teachers had a heavy workload due to flu-outbreak. They also experienced the impediment of usual work implementation. However, there was a shortage of alternative plan such as disposition of an assistant labor force. Under their Job status like this, the health teachers' motivation score was decreased and work exhaustion was increased. Furthermore, they had a lot of relation difficulty with students and school personnel. Therefore, we suggested that in contrast to the usual Job status, there is a need to have a prepared response during school crisis like flu-outbreak such as improved response system in seoul metropolitan education office, simplification or dispersion of administrative work, and temporary call-center for simple inquiries or advices.